A Quantitative Method for Determining Uptake of Silica Nanoparticles in Macrophages by Single Particle Inductively Coupled Plasma–Mass Spectrometry. Issue 3 (25th March 2022) - Rogers, Keegan L.; Cruz‐Hernandez, Angela; Brown, Jared M.
Abstract: Engineered nanomaterials are becoming increasingly ubiquitous in our society, with numerous applications in medicine, consumer products, bioremediation, and advanced materials. As these nanomaterials increase in variety, analyzing their characteristics is of great importance. Single particle inductively coupled plasma–mass spectrometry (SP‐ICP‐MS) is a high‐throughput, sensitive, and robust instrumental analysis method used to simultaneously characterize and quantify nanoparticles in a variety of matrices. One such type of nanoparticle of interest is amorphous silica nanoparticles (SiNPs). SiNPs have widespread use in consumer products such as food and cosmetics and are prime candidates for novel medical applications and uses in environmental bioremediation. Despite their increased use, SiNPs have been shown to have toxicological properties in vitro and in vivo, particularly with regard to the immune system. Because of the potential for increased SiNP exposure in the general public and in occupational settings, examining the relationship that SiNPs have with immune cells such as macrophages to elucidate mechanisms of toxicity is vital. To effectively determine the toxicity of nanoparticles, it is critical to examine dosimetry and the amount of nanoparticles taken up by the cell of interest. Different cell types have different uptake profiles, and varying physicochemical properties govern nanoparticle dosimetry and uptake in cells. Here, we describe a protocol using SP‐ICP‐MS to quantify and characterize the size, size distribution, and amount of SiNPs present in a cell and medium sample. We use a single‐step digestion, which allows for the digestion of biological matrices while simultaneously keeping the SiNPs intact for SP‐ICP‐MS analysis. Clinically, this approach has the potential to be used as a method for analyzing SiNPs in other biological matrices, potentially as a way of defining SiNP uptake as a biomarker in immune‐mediated diseases. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Treatment of cells with silica nanoparticles (SiNPs) and digestion of biological matrices Support Protocol 1 : Culturing RAW 264.7 cells for SiNP uptake assay Support Protocol 2 : Determination of SiNP size via dynamic light scattering Support Protocol 3 : Optimization of sample and ICP‐MS parameters for SP‐ICP‐MS analysis of cells and medium Basic Protocol 2 : Analysis and quantification of SiNP uptake in macrophages with SP‐ICP‐MS